SPECIES DIVERSITY AND MORPHOMETRICS OF SHARKS LANDED AT TANJUNG LUAR FISHING PORT, EAST LOMBOK DISTRICT, WEST NUSA TENGGARA PROVINCE - Parwati, Galuh; Gigentika, Soraya; Damayanti, Ayu Adhita; Hilyana, Sitti (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Sharks have an important role in balancing the ecosystem, but fishing activities that are not yet suitable for catching sharks can cause shark extinction. Therefore, it is necessary to identify the type and size of sharks caught by fishermen. The Tanjung Luar Fishing Port is the largest shark landing site in West Nusa Tenggara Province, making it an ideal research location regarding shark landings. This research analyzes species diversity, conservation status, length distribution, and sex ratio of landed sharks. Data collection in this research was carried out in November 2023 and February-March 2024. Primary data was collected by taking direct measurements of shark length and interviews with fishermen, while secondary data in this research was collected from FIP2B for West Nusa Tenggara Province. This research used species diversity and conservation status analysis, length distribution analysis, and sex ratio analysis. The research results show that shark diversity in 2022 is in the medium category, and in November 2023 and February-March 2024 is in the high diversity category. The lengths of the 3 sharks that dominate, namely Carcharhinus falciformis, Galeocerdo cuvier, and Sphyrna lewini, are almost all below the length of maturity (Lm). For the sex ratio, the sex ratio in 2022 is in a balanced condition, whereas November 2023 and February-March 2024 will be dominated by female sharks. Keywords: Carcharhinus falciformis, length frequency, sex ratio